The Volatilome: A Vital Piece of the Complete Soil Metabolome - Honeker, Linnea K.; Graves, Kelsey R.; Tfaily, Malak M.; Krechmer, Jordan E.; Meredith, Laura K. (Frontiers in Environmental Science, 2021)
Soils harbor complex biological processes intertwined with metabolic inputs from microbes and plants. Measuring the soil metabolome can reveal active metabolic pathways, providing insight into the presence of specific organisms and ecological interactions. A subset of the metabolome is volatile; however, current soil studies rarely consider volatile organic compounds (VOCs), contributing to biases in sample processing and metabolic analytical methods. Therefore, we hypothesize that the volatility of detected compounds measured using current metabolic analytical methods will be lower than undetected compounds, a reflection of missed VOCs. To illustrate this, we examined a peatland metabolomic dataset collected using three common analysis techniques: nuclear magnetic resonance (NMR), gas chromatography-mass spectroscopy (GC-MS), and fourier-transform ion cyclotron resonance mass spectrometry (FT-ICR-MS). We mapped the compounds to three metabolic pathways (monoterpenoid biosynthesis, diterpenoid biosynthesis, and polycyclic aromatic hydrocarbon degradation), chosen for their activity in peatland ecosystems and involvement of VOCs. We estimated the volatility of the compounds by calculating relative volatility indices (RVIs), and as hypothesized, the average RVI of undetected compounds within each of our focal pathways was higher than detected compounds (p < 0.001). Our findings suggest that typical soil metabolomic analytical methods may overlook VOCs and leave missing links in metabolic pathways. To more completely represent the volatile fraction of the soil metabolome, we suggest that environmental scientists take into consideration these biases when designing and interpreting their data and/or add direct online measurement methods that capture the integral role of VOCs in soil systems.